2021
DOI: 10.3389/fbioe.2021.649949
|View full text |Cite
|
Sign up to set email alerts
|

Heterotypic Tumor Spheroids in Agitation-Based Cultures: A Scaffold-Free Cell Model That Sustains Long-Term Survival of Endothelial Cells

Abstract: Endothelial cells (ECs) are an important component of the tumor microenvironment, playing key roles in tumor development and progression that span from angiogenesis to immune regulation and drug resistance. Heterotypic tumor spheroids are one of the most widely used in vitro tumor microenvironment models, presenting improved recapitulation of tumor microenvironments compared to 2D cultures, in a simple and low-cost setup. Heterotypic tumor spheroid models incorporating endothelial cells have been proposed but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 93 publications
(140 reference statements)
0
13
0
Order By: Relevance
“…As pointed out by Franchi-Mendes et al [ 60 ], one of the advantages of spheroid assays is the possibility of focused manipulations with cells to assist elucidation of specific hypotheses. One of more cell types can be genetically altered or specifically labeled enhancing the probative value of the obtained results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out by Franchi-Mendes et al [ 60 ], one of the advantages of spheroid assays is the possibility of focused manipulations with cells to assist elucidation of specific hypotheses. One of more cell types can be genetically altered or specifically labeled enhancing the probative value of the obtained results.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the cadherin-cadherin interactions between neighboring cells tighten the cell-cell connections further and promote additional spheroid compaction. The tissue spheroids sharing many common biological features with a number of normal or diseased tissues, such as vascularized tumors, blood-brain barrier, and cardiac tissue, were produced [ 58 , 59 , 60 ]. The ability to co-culture two or more cell types makes 3D tissue spheroids a promising tool to model heterotypic cell-cell interactions and brings this 3D system to the cutting edge of tissue engineering and drug screening [ 55 , 56 , 61 , 62 ].…”
Section: 3d Tissue Spheroids Comprised Of Ecs and Perivascular Cellsmentioning
confidence: 99%
“…Their results showed that tumor cells are essential for endothelial cell maintenance, and at the optimized ratio of 1:3:10 tumor cell/ fibroblast/endothelial cell, the ratio of endothelial cell area to total area of the spheroid was higher in HCC1954-based spheroids during one month of culture. 29 They found that central colocalization of endothelial cells and fibroblast cells in the spheroids and secretion of collagen I and IV as endothelial cell-relevant extracellular matrix proteins were evident. Based on these results, it seems that spheroid models can be considered as a precious tool for identifying the molecular crosstalk of endothelial cells concerning the tumor microenvironment and its efficacy on the action and response of drugs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The number of vessels was higher in spheroids infiltrated with macrophages than in spheroids without macrophages. In another study, Franchi-Mendes et al 29 explored the essential parameters needed for endothelial cell maintenance in cell culture conditions. For this purpose, they cocultured breast cancer cell line HCC1954 with human fibroblasts and endothelial cells and developed a culture of triple heterotypic spheroids in the long term.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Scaffold-free approaches include using hanging drop plates (Kelm et al, 2003;Guo et al, 2014), low cell attachment plates (Ivanov et al, 2015), and emerging techniques such as magnetic levitation (Türker et al, 2018), ultrasound waves, and acoustic waves. Scaffold-free approaches are easy to perform and can be applied to various cell types (Franchi-Mendes et al, 2021). Microfabrication techniques such as photolithography (Du et al, 2008;Brandenberg et al, 2020) and micromolding (Tekin et al, 2011;Tao et al, 2019) have also been used to create spheroids, allowing the volume and shape of spheroids to be precisely controlled.…”
Section: Introductionmentioning
confidence: 99%